2017
DOI: 10.1136/annrheumdis-2017-211350
|View full text |Cite
|
Sign up to set email alerts
|

Role of erosions typical of rheumatoid arthritis in the 2010 ACR/EULAR rheumatoid arthritis classification criteria: results from a very early arthritis cohort

Abstract: Few patients with early arthritis were classified as RA based on solely the erosion criteria, and of those who did almost all did so at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In the last 20 years, the availability of EACs (19) has certainly allowed to significantly reduce the diagnostic delay, nevertheless a late search for medical care tends to increase this delay (20). At baseline, our population showed clini-cal characteristics in line with similar European cohorts (21,22). The median delay before starting a treatment with a DMARD in general was of 205 days, while the time between the onset of symptoms and the beginning of MTX was of 197 days.…”
Section: Discussionmentioning
confidence: 61%
“…In the last 20 years, the availability of EACs (19) has certainly allowed to significantly reduce the diagnostic delay, nevertheless a late search for medical care tends to increase this delay (20). At baseline, our population showed clini-cal characteristics in line with similar European cohorts (21,22). The median delay before starting a treatment with a DMARD in general was of 205 days, while the time between the onset of symptoms and the beginning of MTX was of 197 days.…”
Section: Discussionmentioning
confidence: 61%
“…In our study, 73% of the ACR/EULAR negative patients displayed ≥3 joints with erosions as compared with 11.7% in the Leiden cohort, 17.4% in the ESPOIR cohort 3 and 5.4% published from a Norwegian Very Early Arthritis Clinic. 16 In the SCQM cohort, patients with early arthritis were included at the discretion of the treating rheumatologist. All were then treated with DMARDs.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining 169 patients not fulfilling the 2010 ACR/EULAR criteria, 55 patients had one or more erosive joints, and 15 patients had three or more erosive joints. 7 It has been suggested that RA is evolving into a milder disease at presentation in the last decades, which is probably partly because of patients presenting themselves earlier in the disease course. 8,9 This trend would decrease the prevalence of erosions at diagnosis and limit diagnostic and/or prognostic value of routine X-HF.…”
Section: Introductionmentioning
confidence: 99%